The Effect The Effect of Ice Breaking on Students' Motivation and Concentration in Science Learning - Suyatman, Suyatman; Syafrial, Syafrial; Nur Sabila Rusydiana (Shautut Tarbiyah-IAIN Kendari, 2026)
This study was motivated by the levels of students learning motivation and learning concentration, particularly in science instruction. During the learning process, students tend to engange in off-task conversations, and their attention is easily diverted to matters outside the learning context. In addition, students often exhibit signs of drowsiness, boredom, disruptive behavior, low enthusiasm, and lack of focus in receiving instructional material. This study aims to analyze the effect of ice-breaking techniques on students’ learning motivation and learning concentration in fifth-grade science learning at MIN 2 Kebumen in the 2024/2025 academic year. The research employed a quantitative approach using a quasi-experimental design. The sampling technique was simple random sampling. The sample consisted of Class V/A as the experimental group and Class V/c as the control group. Data were collected using questionnaires. The research data were analyzed using Multivariate Analysis of Variance (MANOVA) to examine the effect of ice-breaking techniques on students’ learning motivation and learning concentration. The results indicate that ice-breaking techniques have a significant effect on students’ learning motivation and learning concentration at MIN 2 Kebumen, as evidenced by the MANOVA significance value of 0.000, which is lower than 0.05 (0.000 < 0.05).